Relación entre el síndrome de burnout y la resiliencia en el ámbito organizacional - Vera Tudela Miguel de Priego, Gabriela (2021)
The resilience is a key and moderator factor in the prevalence of the burnout syndrome. Because of this, the purpose of this applied review report is to identify the relationship between the burnout syndrome and the resilience. A systematic research was made following the instructions of the PRISMA guide (Urrutia and Bonfill, 2013). The data base reviewed were Scopus and Proquest. Seven articles were selected for the analysis of the results, which evaluated the relationship between the burnout syndrome and the resilience. Most of the selected studies were measured with the Maslach Burnout Inventory and Resilience Scale instruments. As a result, it was found that in fact, there is a significant relationship between the burnout syndrome and the resilience, being higher resilience linked to lower burnout syndrome scores, just as shown on the research results reviewed in this study. Future research should include a third variable beyond the burnout syndrome and the resilience, besides including specialized training programs supporting the resilience development.